2016
DOI: 10.1177/0883073816652233
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine Receptor D5 May Influence Age of Onset

Abstract: The objective was to investigate contribution of the dopamine receptor 5 (DRD5) gene variants in the symptoms of attention-deficit/hyperactivity disorder (ADHD) probands since brain regions identified to be affected in these group of patients have higher expression of the DRD5 receptor. Out of 22 exonic variants, 19 were monomorphic in the Indo-Caucasoid individuals. rs6283 "C" and rs113828117 "A" exhibited significant higher occurrence in families with ADHD probands. Several haplotypes showed biased occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…However, the observed effect of delayed motor development on reduced impulsivity may also be partly due to seeking professional help at an early age. Our earlier study showed higher HA in the late onset group [39]. The present study revealed influence of late onset on increased AI and gradual decrease in HA on a continuous scale, indicating necessity of further analysis in larger cohort.…”
Section: Discussionsupporting
confidence: 43%
“…However, the observed effect of delayed motor development on reduced impulsivity may also be partly due to seeking professional help at an early age. Our earlier study showed higher HA in the late onset group [39]. The present study revealed influence of late onset on increased AI and gradual decrease in HA on a continuous scale, indicating necessity of further analysis in larger cohort.…”
Section: Discussionsupporting
confidence: 43%
“…We do know that upregulation of DRD1 , DRD3 , and DRD5 expression in blood, along with alterations in the expression of other dopaminergic signaling genes, has been associated with lower resilience to stressful events and other psychological parameters, including personality, depression, anxiety, and intelligence, in age, sex, and race-matched individuals [ 11 ]. We also know that increasing binding of D1 receptors has been associated with younger age in suicide [ 12 ], and DRD5 variants have been associated with age of onset in pediatric attention-deficit/hyperactivity disorder (ADHD) patients [ 13 ]. Such information further supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…CDEGs fabp7 and endod1 were positively correlated with brain growth in the three families and are thought to play an important role in the development of the grass carp nervous system. Attention de cit hyperactivity disorder (ADHD) has been linked to variations in the drd5 (dopamine receptor D5) gene in humans, and ADHD patients have higher drd5 expression in affected brain regions [26,27]. Drd5 was the only CDEG found to be negatively associated with growth in grass carp brain.…”
Section: Growth-related Cdegs In Grass Carp Brainmentioning
confidence: 99%